ANALISIS AKTOR IMPLEMENTASI KEBIJAKAN BRT (BUS RAPID TRANSIT) SEMARANG DALAM MENGATASI KEMACETAN LALU LINTAS DI KOTA SEMARANG - Novriyaldi Novriyaldi; Nina Widowati; Maesaroh Maesaroh (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro)
Transport has a role very strategically in the process of infrastructure development activities in urban areas. The emergence of the policy Bus Rapid Transit in Semarang was triggered by the efforts of the improvement of public transport is conducted by the Government of Semarang, Department of Transportation, and Public service Agencies Bus Rapid Transit Semarang. The research aims to analyze the role of actors and explain the driving factors and inhibiting factors for the success of the actor's role in achieving the objectives of the implementation of the policy BRT Semarang in addressing traffic congestion in the City of Semarang. This research uses descriptive qualitative research methods, data collection techniques through interviews, observation, and documentation. The results show that the role of the society is still relatively small because there is no interest and power possessed by the community as an actor in implementing Semarang's BRT policy, the inhibiting factors for the success of the actor's role are still not optimal in participation in supervision carried out by the government, human resources owned by the Semarang BRT Public Service Agency and participation, accessibility and the level of community knowledge in the implementation of Semarang's BRT policy. Suggestions that researchers can give, To increase the role of the community, the Government, the Department of Transportation and the Semarang BRT Public Service Agency need to provide socialization for the community. The Semarang City Government needs to increase participation in supervision, the BRT Public Service Agency needs to increase human resources for drivers in supporting performance in the operation of the Semarang BRT and in increasing participation, accessibility and the level of community knowledge all the main actors need to provide support and guidance.